Pengaruh Kompetensi Profesional Guru Terhadap Minat Belajar Siswa pada Mata Pelajaran Matematika Kelas VI dI SDN 016 SITUGAL - Destri Pajrya (Universitas Muhammadiyah Enrekang, 2023)
Every element of research undoubtedly includes goals and objectives. This experimental study aims to find out how teacher professional competence influences students' interest in learning in mathematics subjects. A